The Impact of E-Service Quality Towards Customer Repurchase Intention in The Case of Traveloka. - Orlando A. Y. Samuel (iBuss Management, 2020)
The importance of electronic service quality (E-Service Quality) in order to maintain and develop the customer repurchase intention as well as to stay competitive in the market. This research is being conducted in order to understand better and deeper about the influence of e-service quality towards customer repurchase intention. E-service quality will be used as a variable which represented by web design/functionality, responsiveness, reliability, enjoyment, ease of use, security and customization towards customer repurchase intention in Traveloka.This research uses online questionnaire to gather the data from various Traveloka’s customer. The data that is gathered have to passed validity and reliability test, classical assumption test and finally through multiple linear regression.The findings of the research suggest that e-service quality have an impact towards customer repurchase intention on Traveloka. From those e-service quality elements, reliability is the most impactful factor that influence customer repurchase intention on Traveloka. Keywords: E-Service Quality, Repurchase Intention, Traveloka, Service Quality, E-commerce